Surveillance of life-long antibiotics: a review of antibiotic prescribing practices in an Australian Healthcare Network - Lau, Jillian S. Y.; Kiss, Christopher; Roberts, Erika; Horne, Kylie; Korman, Tony M.; Woolley, Ian (Annals of clinical microbiology and antimicrobials, 2017)
Background The rise of antimicrobial use in the twentieth century has significantly reduced morbidity due to infection, however it has also brought with it the rise of increasing resistance. Some patients are on prolonged, if not “life-long” course of antibiotics. The reasons for this are varied, and include non-infectious indications. We aimed to study the characteristics of this potential source of antibiotic resistance, by exploring the antibiotic dispensing practices and describing the population of patients on long-term antibiotic therapy. Methods A retrospective cross-sectional study of antibiotic dispensing records was performed at a large university hospital-based healthcare network in Melbourne, Australia. Outpatient prescriptions were extracted from the hospital pharmacy database over a 6 month period in 2014. Medical records of these patients were reviewed to determine the indication for prescription, including microbiology, the intended duration, and the prescribing unit. A descriptive analysis was performed on this data. Results 66,127 dispensing episodes were reviewed. 202 patients were found to have been prescribed 1 or more antibiotics with an intended duration of 1 year or longer. 69/202 (34%) of these patients were prescribed prolonged antibiotics for primary prophylaxis in the setting of immunosuppression. 43/202 (21%) patients were prescribed long-term suppressive antibiotics for infections of thought incurable (e.g. vascular graft infections), and 34/43 (79%) were prescribed by Infectious Diseases doctors. 66/202 (33%) patients with cystic fibrosis were prescribed prolonged courses of macrolides or fluoroquinolones, by respiratory physicians. There was great heterogeneity noted in indications for prolonged antibiotic courses, as well as antibiotic agents utilised. Conclusion Our study found that that continuous antibiotic therapy represented only a small proportion of overall antibiotic prescribing at our health network. Prolonged courses of antibiotics were used mainly to suppress infections thought incurable, but also as primary and secondary prophylaxis and as anti-inflammatory agents. More research is needed to understand the impact of long-term antibiotic consumption on both patients and microbial ecology.